Effect of short-term intensive insulin therapy on α-cell function in patients with newly diagnosed type 2 diabetes. Issue 14 (April 2020) - Zheng, Hai-Lan; Xing, Yan; Li, Fan; Ding, Wei; Ye, Shan-Dong
Abstract : Abstract: The effect of intensive insulin therapy on hyperglucagonemia in newly diagnosed type 2 diabetes (T2DM), and its associations with β-cell function, has not been elucidated. This study assessed the effect of 12 weeks of intensive insulin therapy on hyperglucagonemia in newly diagnosed T2DM and its associations with β-cell function, with reference to the effects of 12 weeks of oral hypoglycemic agents (OHAs). One hundred eight patients with newly diagnosed T2DM were enrolled from January 2015 to December 2015. The patients were randomly divided to receive, for 12 weeks, either intensive insulin therapy or OHAs. Meal tolerance tests were conducted at baseline before treatment (0 week), at 12 weeks (end of treatment), and 12 months after the initiation of treatment. The levels of glucagon, proinsulin, C-peptide (CP), and blood glucose were measured at timepoints 0, 30, and 120 minutes during the meal tolerance test. Intensive insulin treatment was associated with a decrease in glucagon levels (at 0, 30, and 120 minutes) and proinsulin/CP, and an increase in the insulin-secretion index ΔCP30 /ΔG30 and ΔCP120 /ΔG120, at 12 weeks and 12 months during the follow-up, compared with the corresponding effects of OHAs. Intensive insulin therapy could reduce but failed to normalize glucagon levels at 12 weeks. There were no correlations between the change of percentages in total area under the curve of glucagon and other glycemic parameters (proinsulin/CP; ΔCP30 /ΔG30 ; or ΔCP120 /ΔG120 ). Patients who received intensive insulin therapy were more likely to achieve their target glycemic goal and remission, compared with those who received OHAs. Short-term intensive insulin therapy facilitates the improvement of both β-cell and α-cell function in newly diagnosed T2DM mellitus. Decline of β-cell secretion and concomitant α-cell dysfunction may both be involved in the pathogenesis of T2DM. Abstract : Supplemental Digital Content is available in the text